Destination Management for Sustainable Tourism: A Case Study of Bungamati and Khokana - Ghimire, Ananda; Baral, Deep Kumar (Interdisciplinary Journal of Innovation in Nepalese Academia, 2022)
Development is a peaceful transformation of all round betterment. Tourism is one of the best means to attain development at the local level. To be sustainable, it must be accepted by the local people. The local people need to be aware of tourism, involve in tourism activities, realize its benefit, and impacts to be sustainable. Nepal, as a destination, includes many destinations within it such as Everest region, Annapurna region, Pokhara, Chitwan, and so on. Kathmandu Valley as a destination contains seven World Heritage Sites, which is a world record by itself. Among several local heritage sites, culturally rich Newar villages of Bungamati and Khokana have all the basic elements to be a tourism destination. The comparative analysis of these two destinations analyze the local perception about tourism, sustainable tourism, impacts and benefits of tourism and identifies the variables and factors needed to be studied to be a sustainable tourism destination.